Quality Control of Shoe Products Using the New Seven Tools Method and Root Cause Analysis - Fuadah, Layin; Rochmoeljati, Rr. (Journal La Multiapp, 2025)
This study aims to analyze and control product defects in shoes produced by PT XYZ using the New Seven Tools method and Root Cause Analysis (RCA). The research method applied is descriptive with both qualitative and quantitative approaches. Primary data were obtained through observations and interviews, while secondary data consisted of production documents and defect records collected from June 2024 to January 2025. The analysis results show that defect rates exceeded the company’s standard threshold (2%), particularly in the sewing and lasting processes. By utilizing tools such as the Affinity Diagram, P-Chart, Tree Diagram, Matrix Diagram, and Process Decision Program Chart (PDPC), the study identified that the main contributing factors to defects stemmed from human, method, machine, material, and environmental aspects. RCA revealed that the root causes included insufficient training, non-compliance with standard operating procedures (SOP), suboptimal equipment, and unergonomic working conditions. The study proposed 33 improvement actions, of which 28 were deemed feasible for implementation. These findings are expected to help reduce the number of defective products and improve overall production quality.